2013
DOI: 10.1111/pan.12117
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of esmolol on myocardial ischemic injury during open heart surgery in children

Abstract: SummaryObjectives: To investigate the efficacy of esmolol in protecting the myocardium from ischemia during pediatric cardiac surgery. Background: Esmolol, an ultra-short acting beta 1-adrenoceptor blocker, reduces myocardial injury in adult cardiac operations. However, this technique is rarely used in pediatric cardiac surgery. Methods: Thirty children with ventricular septal defect were randomly allocated to the esmolol group and the control group. Patients received intravenous esmolol (0.05 mgÁkg À1 ÁminÀ1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Esmolol has been used during CPB in children and it was demonstrated that patients of the esmolol group had lower creatine kinase, troponin I and lactate levels and less need for inotropic support. Moreover, myocardial structure was better preserved (Kuhn-Regnier et al, 1999 ; Gui et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Esmolol has been used during CPB in children and it was demonstrated that patients of the esmolol group had lower creatine kinase, troponin I and lactate levels and less need for inotropic support. Moreover, myocardial structure was better preserved (Kuhn-Regnier et al, 1999 ; Gui et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…[15] In one of the studies in which esmolol infusion was used for children operated on for the treatment of VSD, a dose of 0.05 mg/kg/min was used until the CPB, 0.03 mg/kg/min during the bypass and 0.03-0.05 mg/kg/min after CPB. [16] In our clinical practice, we have been using esmolol infusion and, since we have experienced that doses higher than 0.07 mg/kg/min may negatively affect the hemodynamic parameters, we have fixed the dose at 0.05 mg/kg/min. During CPB, the dose is reduced to 0.025 mg/kg/min.…”
Section: Discussionmentioning
confidence: 99%
“…Among infants with SVT, esmolol is commonly used, along with other adjunctive therapies, as an abortive medication in the acute care setting 45 . It has also been used as an adjunct to anesthesia during cardiac surgeries in children requiring cardiopulmonary bypass 49 …”
Section: Esmolol (Class Ii)mentioning
confidence: 99%